Bermain Sambil Belajar Berwirausaha Mengasah Keterampilan dan Kemampuan Entrepreneurship Melalui Craft Day - Sukma, Septi Ambar Indraningtia; Widodo, Slamet; Lembang Jaya, Muhamad; Fitriani, Lia Firdia; Ayu Agustin, Wilujeng; Noratama, Gilang; Nur Azizah, Firda Nikmah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
ABSTRACT Character formation in the world of education can start from early childhood and elementary school education according to Mulyani, 2012 in (Badawi, 2023). Early childhood education must introduce entrepreneurial values ​​and character (Saaadah & Nurjaman, 2023). Efforts to foster entrepreneurial character can be done through entrepreneurial activities from an early age, and this can be applied in Craft Day activities which can be an opportunity for students to be creative in producing work and selling their own work. The aim of this program is to introduce the concept of entrepreneurship to elementary school and Madrasah Ibtidaiyah students. To provide an understanding of the basic concepts of entrepreneurship related to planning, marketing and sales in a simple way to elementary school and Ibtidaiyah Madrasah students. The program